A Sierra Leone 2021 Midwifery Clinical Training Needs Assessment: A Call to Action to Augment Clinical Precepting. Issue 1 (13th February 2023) - Sonnie, Mustapha; Kella, Frederica; Stern, Amy; Mannino, Clelia Anna; Adelman, Sara; Euller, Laura; Forbush, Leigh; Mann, Julie; van de Water, Brittney; Falahee, Bryn; Sayeed, Sadath; Ewing, Helen; et al.
Objective: Sierra Leone has one of the highest maternal mortality and infant mortality rates globally. We share findings from a Midwifery Clinical Training Needs Assessment, conducted in 2021 as a collaboration between the Government of Sierra Leone and Seed Global Health. The assessment identified existing needs and gaps in midwifery clinical training at health facilities in Sierra Leone from various stakeholders' perspectives. Methods: The descriptive needs assessment utilized mixed methods, including surveys, focus group discussions (FGDs), interviews, and reviews of maternal medical records. Results: The following showed needs and gaps in labor and delivery management; record keeping; triage processes; clinical education for students, recent graduates, and preceptors; and lack of infrastructure and resources. Conclusion: The knowledge gained from this needs assessment can further the development of midwifery clinical training programs in Sierra Leone and other low-income countries facing similar challenges. We discuss the implication of our findings.